2014
DOI: 10.1093/deafed/enu040
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Social Competence in Young Children With and Without Hearing Loss: A Dynamic Systems Framework

Abstract: This study compared levels of social competence and language development in 74 young children with hearing loss and 38 hearing peers aged 2.5-5.3 years. This study was the first to examine the relationship between oral language and social competence using a dynamic systems framework in children with and without hearing loss. We hypothesized that, due to deficits in oral language, children who were deaf would display lower levels of social competence than their hearing peers. Furthermore, language age would pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…In this study, 11.1% of the fathers are illiterate and 82.725% of them are primary school graduates, respectively. These results are consistent with findings of Hoffman et al (2015).…”
Section: Hopelessness Levels In Children With and Without Hearing Impsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, 11.1% of the fathers are illiterate and 82.725% of them are primary school graduates, respectively. These results are consistent with findings of Hoffman et al (2015).…”
Section: Hopelessness Levels In Children With and Without Hearing Impsupporting
confidence: 93%
“…However, Sahin (2009) found that educational level of father has no impact on hopelessness levels of healthy children. In addition, Hoffman, Quittner, and Cejas (2015) determined that educational levels of families who have children with hearing impairment are quite low. In this study, 11.1% of the fathers are illiterate and 82.725% of them are primary school graduates, respectively.…”
Section: Hopelessness Levels In Children With and Without Hearing Impmentioning
confidence: 99%
“…25,38 The results strongly supported the dynamic systems model, which posits that deficits in one area of development have cascading effects on other areas. 15,17,18 In particular, children with hearing loss, who have delays in language, may be at increased risk for delays in social competence and related developmental domains. Our results showed that children with CIs had significant delays in social competence across time compared to their hearing peers, even 8 years after implantation .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Children with hearing loss, who have delays in language, may be at increased risk for delays in social competence and related sequelae. 11-15 The purpose of this study was to compare social competence over time in children with cochlear implants (CIs) and their hearing peers over 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing impairment may cause many problems in the development of the child. Since children with hearing impairment don't have fully developed speaking and listening skills and they are unable to speak functionally, they have deficiencies in terms of social and communicational skills and it is quite possible for these children to encounter difficulties in communication with the outside world (Hummel & Schirman, 1984;Leigh & Stinson, 1991;Van Oyen et al, 2001;Scheetz, 2004;Hoffman et al, 2015). The negativities experienced by hearing-impaired children when entering the socialization process without the chance to choose differ from their peers and these negativities considered as unreachable boundaries despair them; and therefore, aggressive behaviors, low self-esteem, despair, worthlessness and the feelings of anger and frustration arise in these children.…”
Section: Introductionmentioning
confidence: 99%